Analysis of Tax Law on Imported Goods in Indonesian Customs Territory - Raudhatul Jannah; Agung Satrio; Sahril Napiputulu (ISNU Sumatera Utara, 2025)
This study aims to analyze the legal aspects of taxation on imported goods entering the Indonesian customs territory. The focus of the study includes the juridical foundation, the mechanism of imposing taxes, and the legal implications for violations of import regulations. In the context of national law, the imposition of taxes on imported goods is regulated in the Customs Law and the Value Added Tax Law, which provide a legal basis for the imposition of import duties, Value Added Tax (VAT), Income Tax (PPh) Article 22, and Import Duties for Security Measures (BMTP). This study uses a normative juridical method with a legislative approach and conceptual analysis. The results of the analysis show that although the existing legal framework is sufficiently comprehensive, there are still challenges in terms of law enforcement and inter-regulatory synchronization. This study recommends increased coordination between law enforcement agencies and the updating of technical regulations to adapt to the dynamics of international trade.